Central Retinal Vein Occlusion with Therapeutic Level of Anticoagulation - Sarwat Salim; Wai-Ching Lam; Wahid Hanna (Case Reports in Medicine)
Purpose. To describe a patient with two episodes of deep venous thrombosis and factor V Leiden mutation who presented with central retinal vein occlusion (CRVO) despite prophylactic use of warfarin sodium (Coumadin). Methods. A case report of a 44-year-old woman with a history of recurrent deep venous thrombosis and Factor V Leiden mutation was placed on lifelong prophylactic therapy with warfarin. The patient presented with CRVO in the left eye despite therapeutic levels of warfarin. Results. Extensive systemic evaluation disclosed high titers for antinuclear antibody (ANA). Conclusion. Systemic anticoagulation with warfarin may not preclude further thrombotic episodes. In younger patients presenting with retinal vein occlusion and pre-existing multiple thrombophilic risk factors, a multidisciplinary approach is recommended to explore other therapeutic options to avoid further thromboembolic complications.